2005
DOI: 10.1016/j.freeradbiomed.2004.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of the human Lon protease impairs mitochondrial structure and function and causes cell death

Abstract: Lon now emerges as a major regulator of multiple mitochondrial functions in human beings. Lon catalyzes the degradation of oxidatively modified matrix proteins, chaperones the assembly of inner membrane complexes, and participates in the regulation of mitochondrial gene expression and genome integrity. An early result of Lon downregulation in WI-38 VA-13 human lung fibroblasts is massive caspase 3 activation and extensive (although not universal) apoptotic death. At a later stage, the surviving cells fail to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
155
1
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(166 citation statements)
references
References 60 publications
8
155
1
1
Order By: Relevance
“…Even though treatment with cholesterol and palmitate, and transfection with Loni finally caused hepatic gluconeogenesis to increase and induced insulin resistance, the process that leads to insulin resistance does not seem to be identical. Bota et al have shown that downregulation of lon protease in WI-38 VA-13 human lung fibroblast leads to mitochondrial dysfunction and apoptosis [14]. We observed mitochondrial dysfunction, but did not see cell death by transfection with Loni (Fig.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…Even though treatment with cholesterol and palmitate, and transfection with Loni finally caused hepatic gluconeogenesis to increase and induced insulin resistance, the process that leads to insulin resistance does not seem to be identical. Bota et al have shown that downregulation of lon protease in WI-38 VA-13 human lung fibroblast leads to mitochondrial dysfunction and apoptosis [14]. We observed mitochondrial dysfunction, but did not see cell death by transfection with Loni (Fig.…”
Section: Discussionmentioning
confidence: 47%
“…Indeed, in the absence of Pim1, yeast becomes respiratorydeficient because it is unable to maintain mDNA, leading to accumulatin of electron-dense inclusion bodies in the mitochondrial matrix [12]. Finally, in humans, lon protease is associated with mitochondrial biogenesis; lon protease deficiency is responsible for the abnormal structure of mitochondria [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…In human fibroblast cells, depletion of Lon over 4 d resulted in apoptotic cell death (37,38), whereas Lon knockdown in human colon carcinoma cells allows survival for at least 15 d (18). Thus, the effects of Lon depletion may be species-or cell type-specific.…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian mitochondria, LON has been shown to degrade aconitase, an Fe/S protein, the steroidogenic acute regulatory protein (StAR), and the mitochondrial transcription factor A (TFAM) Granot et al 2007;Matsushima et al 2010). LON appears to play a role in cellular aging as in aged mice, the levels of functional LON decline, concomitant with an increase in oxidatively damaged mitochondrial proteins and increased mitochondrial dysfunction (Bota et al , 2005. Furthermore, overexpression of Lon in the fungal aging model, Podospora anserina, results in an increased lifespan without affecting respiration, growth, or fertility (Luce and Osiewacz 2009).…”
Section: Atp-dependent Proteolysis In the Mitochondrial Matrixmentioning
confidence: 99%